Reasonableness and Effectiveness in Argumentative Discourse - van Eemeren, Frans H. author. aut Link
XXIV, 904 p. 35 illus.
Keywords: This volume presents 50 contributions on the themes of reasonableness and effectiveness and their connections, which are central issues in argumentation theory. It discusses van Eemeren’s views on the study of argumentation; the approach to argumentation adopted in pragma-dialectics; pragma-dialectical perspectives on the dialectical and pragmatic dimensions of argumentative discourse; the notion of strategic maneuvering; the pragma-dialectical method of analyzing argumentative discourse; the treatment of fallacies as violations of rules for critical discussion; pragma-dialectical views on context, the role of logic, verbal indicators of argumentative moves and argument schemes; and the process of writing and rewriting argumentative texts. The pragma-dialectical quantitative approach to empirical research on argumentative discourse is illustrated by reporting on selected, illustrative experimental studies, as well as qualitative studies of historical cases.